2001
DOI: 10.1083/jcb.200011001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p53 function in normal human mammary epithelial cells increases sensitivity to extracellular matrix–induced apoptosis

Abstract: Little is known about the fate of normal human mammary epithelial cells (HMECs) that lose p53 function in the context of extracellular matrix (ECM)–derived growth and polarity signals. Retrovirally mediated expression of human papillomavirus type 16 (HPV-16) E6 and antisense oligodeoxynucleotides (ODNs) were used to suppress p53 function in HMECs as a model of early breast cancer. p53+ HMEC vector controls grew exponentially in reconstituted ECM (rECM) until day 6 and then underwent growth arrest on day 7. Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
(68 reference statements)
4
32
0
Order By: Relevance
“…Our findings identify a novel role for α3β1 integrin in promoting the survival of epidermal keratinocytes through a MEK/ERK signaling pathway. This pro-survival role for α3β1 in keratinocytes is clearly distinct from previously described roles in cells of distinct origin or transformation status, where α3β1 and/or its laminin ligands were shown either to promote apoptosis (Seewaldt et al, 2001;Sato et al, 1999) or to promote cell survival in a MEK/ERK-independent manner (Gu et al, 2002). Although it is known that LN-5 promotes keratinocyte survival in the epidermis (Ryan et al, 1999;Nguyen et al, 2000), the relative roles of the LN-5-binding integrins α3β1 and α6β4 and the signaling pathways involved are unclear.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings identify a novel role for α3β1 integrin in promoting the survival of epidermal keratinocytes through a MEK/ERK signaling pathway. This pro-survival role for α3β1 in keratinocytes is clearly distinct from previously described roles in cells of distinct origin or transformation status, where α3β1 and/or its laminin ligands were shown either to promote apoptosis (Seewaldt et al, 2001;Sato et al, 1999) or to promote cell survival in a MEK/ERK-independent manner (Gu et al, 2002). Although it is known that LN-5 promotes keratinocyte survival in the epidermis (Ryan et al, 1999;Nguyen et al, 2000), the relative roles of the LN-5-binding integrins α3β1 and α6β4 and the signaling pathways involved are unclear.…”
Section: Discussionmentioning
confidence: 67%
“…All experiments were performed on mass cultures. Double retroviral transductions Expression and selection of two retroviral constructs are adapted from previously published methods (Seewaldt et al, 2001b). Construction of retroviral vectors containing either the coding sequences for AKT1-Myr or AKT-DD was as described (Seewaldt et al, 1995).…”
Section: Cell Culture Conditions and Retroviral Transductionmentioning
confidence: 99%
“…Three T-75 flasks of each cell type were grown to 50% confluency, treated for 1 h with 1.0 mM Tam, harvested as previously described (Seewaldt et al, 2001b), resuspended in immunoprecipitation buffer (homogenization buffer with 1.0% Triton X-100, 0.1 mM PMSF, 0.1 mM TLCK, 0.1 mM TPCK, 1 mg/ml pepstatin, 1 mg/ml leupeptin, 15 mg/ml calpain inhibitor I, 1 mg/ml aprotinin, 50 mg/ml bestain), aliquoted, and stored at À701C until use. The lysate was separated by 10% SDS-PAGE and transferred to a PVDF membrane that was blocked overnight with 10% BSA (w/v) dissolved in Trisbuffered saline with 0.1% Tween-20 (TTBS).…”
Section: Sds-page and Western Analysismentioning
confidence: 99%
“…As a result, it is uncertain whether Tam is able to target the elimination of acutely damaged, ER-poor cells or whether Tam's action is restricted to mammary epithelial cells that express high levels of ER. We have previously shown that 1.0 mM Tam rapidly promotes apoptosis in acutely damaged, ER-poor HMECs but only induces growth arrest in HMEC controls Seewaldt et al, 2001). Here we further investigated the molecular mechanism of Tam-induced apoptosis in acutely damaged HMECs.…”
Section: Introductionmentioning
confidence: 99%